Modern condition and the prospect of development of the health-therapeutic complex in the South-Kazakhstan region (Journal of Geography and Environmental Management, 2019)
The priority in the development of sanatorium and resort sector is not only economic efficiency butalso social impact in the Republic of Kazakhstan. The development and improvement of the functioningof the sanatorium and resort services market of the Republic of Kazakhstan is one of the main topicalissues for analysis and evaluation.Nowadays the international tourism services is a gigantic mechanism with a multi-billion dollar turnoverand a fierce competition. The primary task is to define a tourism product that has features unique toKazakhstan and will be in demand. One of the most popular types of tourism activity in modern conditionsis health tourism. The article reveals the current state and prospects for its development.Kazakhstan has wide opportunities for the development of health– therapeutic complex. The basisfor the development of a health complex is a unique natural environment, an abundance of mineralsprings, a lot of therapeutic mud and other factors.The development of medical and sanitary complexes in South Kazakhstan region agreed with theavailability of raw materials. Health-therapeutic tourism is becoming one of the promising sectors of theeconomy of the South-Kazakhstan region. The state of medical and health tourism in the South Kazakhstanregion is examined.